Kisspeptin-10 binding to Gpr54 in osteoclasts prevents bone loss by activating Dusp18-mediated dephosphorylation of Src - Zhenxi Li; Xinghai Yang; Ruifeng Fu; Zhipeng Wu; Shengzhao Xu; Jian Jiao; Ming Qian; Long Zhang; Chunbiao Wu; Tianying Xie; Jiqiang Yao; Zhixiang Wu; et al. (Nature Communications)
Abstract Osteoclasts are over-activated as we age, which results in bone loss. Src deficiency in mice leads to severe osteopetrosis due to a functional defect in osteoclasts, indicating that Src function is essential in osteoclasts. G-protein-coupled receptors (GPCRs) are the targets for ∼35% of approved drugs but it is still unclear how GPCRs regulate Src kinase activity. Here, we reveal that GPR54 activation by its natural ligand Kisspeptin-10 (Kp-10) causes Dusp18 to dephosphorylate Src at Tyr 416. Mechanistically, Gpr54 recruits both active Src and the Dusp18 phosphatase at its proline/arginine-rich motif in its C terminus. We show that Kp-10 binding to Gpr54 leads to the up-regulation of Dusp18. Kiss1, Gpr54 and Dusp18 knockout mice all exhibit osteoclast hyperactivation and bone loss, and Kp-10 abrogated bone loss by suppressing osteoclast activity in vivo. Therefore, Kp-10/Gpr54 is a promising therapeutic target to abrogate bone resorption by Dusp18-mediated Src dephosphorylation.